2010
DOI: 10.1093/molbev/msq088
|View full text |Cite
|
Sign up to set email alerts
|

Using Time-Structured Data to Estimate Evolutionary Rates of Double-Stranded DNA Viruses

Abstract: Double-stranded (ds) DNA viruses are often described as evolving through long-term codivergent associations with their hosts, a pattern that is expected to be associated with low rates of nucleotide substitution. However, the hypothesis of codivergence between dsDNA viruses and their hosts has rarely been rigorously tested, even though the vast majority of nucleotide substitution rate estimates for dsDNA viruses are based upon this assumption. It is therefore important to estimate the evolutionary rates of dsD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
297
4
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(329 citation statements)
references
References 76 publications
25
297
4
3
Order By: Relevance
“…Moreover, our findings are consistent with recent studies supporting the suggestion that the evolutionary rates of some dsDNA viruses are comparable to those of RNA and ssDNA viruses (Babkin & Shchelkunov, 2008;Firth et al, 2010;Hughes et al, 2010).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, our findings are consistent with recent studies supporting the suggestion that the evolutionary rates of some dsDNA viruses are comparable to those of RNA and ssDNA viruses (Babkin & Shchelkunov, 2008;Firth et al, 2010;Hughes et al, 2010).…”
supporting
confidence: 93%
“…The analyses revealed that the DNA polymerase, UL34 and UL18 genes of CFPHV were already under purifying selection with an overall ratio of non-synonymous to synonymous substitutions (d N /d S ) of 0.17, 0.24 and 0.28, respectively, and only the glycoprotein B gene had an overall d N /d S of~1, indicative of no significant selective pressure. Moreover, our findings are consistent with recent studies supporting the suggestion that the evolutionary rates of some dsDNA viruses are comparable to those of RNA and ssDNA viruses (Babkin & Shchelkunov, 2008;Firth et al, 2010;Hughes et al, 2010).Substitution rates of viruses are a complex product of the underlying mutation rate, generation time, effective population size and fitness (Duffy et al, 2008). Factors such as changing environments, high transmission rates and high replication rates can inflate virus evolutionary rates (Duffy et al, 2008;Firth et al, 2010;Hughes et al, 2010).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…How genetic variability affects DNA viruses as compared to RNA viruses is a critical, pertinent question in evolutionary virology (Domingo et al, 2001a, b;Firth et al, 2010). Drake compared several cellular and viral DNAs and concluded that they all displayed a mean rate of 0.003 mutations introduced per genome and round of replication (Drake, 1991), and that the value for HSV-1 was comparable to that for other DNA-based genomes (Drake & Hwang, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…VZV genome has been noted to be highly conserved (4~7). The herpesviruses in that the natural mutation rate was estimated to range between 10 -6 and 10 -7 substitution/ site/year (8,9), while that of herpes simplex virus type 1 ranged between 10 -4 and 10 -5 substitution/site/year (7,9).…”
Section: Coding Region Of the Vzv Genomes Consists Of 74 Openmentioning
confidence: 99%